Oak forest flora (Quercus: Fagaceae) of two ravines of the Puebla city, Mexico - Gutiérrez Pacheco, Victor; Silva Gómez, Sonia Emilia; Varela Olguín, Laura Leonor (Instituto de Ecología, A.C., 2021)
The Puebla city ravines have a relic of oak forest (Quercus: Fagaceae) that is subject to strong human pressures. Despite the importance that this relict represents for a city lacking in wooded areas, there is no information on its richness, diversity, and geographical affinity. Hence the objective of this work, to carry out an inventory of the vascular flora components, determining the current geographic distribution patterns of the families, genera and species, and specify the richness, diversity and floristic similarity of El Conde and Malinalli ravines. This was done through field trips and botanical specimen collection, using the Margalef, Pielou and Simpson indices to estimate alpha diversity patterns and the Sorensen Similarity Index to determine beta diversity. A list of 105 species was obtained, grouped into 81 genera and 40 families, and both ravines have a medium to high alpha and beta diversity. Because to the ecosystem services that wooded areas provide to urban areas, knowledge of the forest should be deepened, and the study extended to other ravines as a step towards recovery, remediation, management and conservation.